Organic food in the aspect of food safety in Poland and in the European Union - Małgorzata Szymańska-Brałkowska; Ewa Malinowska (Economic and Environmental Studies (E&ES), 2014)
The conducted research shows the idea of organic food in the area of food safety system in the European Union. Authors focus on the reasons why customers decide to buy and consume organic food. The aim of this study is to present the reasons of purchasing organic food and its definition for a customer. The work presents the main threats that are connected with the production of organic food in the area of sustainable agriculture. Moreover the paper shows the current situation regarding organic food and farming in Poland and in the European Union.
Keywords: 330; organic food; food safety; food safety system; sustainable agriculture